Trophic regions of a hydrothermal plume dispersing away from an ultramafic‐hosted vent‐system: Von Damm vent‐site, Mid‐Cayman Rise. (16th April 2013) - Bennett, Sarah A.; Coleman, Max; Huber, Julie A.; Reddington, Emily; Kinsey, James C.; McIntyre, Cameron; Seewald, Jeffrey S.; German, Christopher R.
Abstract: [1] Deep‐sea ultramafic‐hosted vent systems have the potential to provide large amounts of metabolic energy to both autotrophic and heterotrophic microorganisms in their dispersing hydrothermal plumes. Such vent‐systems release large quantities of hydrogen and methane to the water column, both of which can be exploited by autotrophic microorganisms. Carbon cycling in these hydrothermal plumes may, therefore, have an important influence on open‐ocean biogeochemistry. In this study, we investigated an ultramafic‐hosted system on the Mid‐Cayman Rise, emitting metal‐poor and hydrogen sulfide‐, methane‐, and hydrogen‐rich hydrothermal fluids. Total organic carbon concentrations in the plume ranged between 42.1 and 51.1 μM (background = 43.2 ± 0.7 μM ( n  = 5)) and near‐field plume samples with elevated methane concentrations imply the presence of chemoautotrophic primary production and in particular methanotrophy. In parts of the plume characterized by persistent potential temperature anomalies but lacking elevated methane concentrations, we found elevated organic carbon concentrations of up to 51.1 μM, most likely resulting from the presence of heterotrophic communities, their extracellular products and vent larvae. Elevated carbon concentrations up to 47.4 μM were detected even in far‐field plume samples. Within the Von Damm hydrothermal plume, we have used our data to hypothesize a microbial food web in which chemoautotrophy supports a heterotrophic community of microorganisms. Such an active microbial food web would provide a source of labile organic carbon to the deep ocean that should be considered in any future studies evaluating sources and sinks of carbon from hydrothermal venting to the deep ocean. Key Points: Carbon cycling in an ultramafic hosted hydrothermal plume Identification of methanotrophy as a result of lower than expected methane Hypothesis of a microbial food web within a dispersing plume